Обучение технике рукопашного боя на основе использования возможностей информационно-методической программы «Правозащитник» . - Данильченко, В. А.; Хлевна, Ю. Л.; Danil’chenko, V. A.; Khlevna, Y. L. (Східноєвропейський національний університет імені Лесі Українки, 2012)
Систематизированы данные по обучению технике двигательных действий курсантов. Разработана компьютерная информационно-методическая программа по обучению основам рукопашного боя. Установлено, что информационные технологии становятся основой для формирования нового типа среды обучения. Представлен теоретический и практический материал по вопросам обучения технике двигательных действий с использованием информационных технологий. Описана структура разработанной информационно-методической программы. Information is systematized on teaching technique of motive actions of students. The computer is developed informatively-methodical program on bases of hand-to-hand fight. It is set that information technologies become basis for forming of new type of teaching environment. Theoretical and practical material on questions of teaching of technique of motive actions with the use of information technologies is presented. A structure is described developed to informatively-methodical programs.
Teaching Technique of Hand-to-hand Fight on Basis of use of Possibilities of Informative-Methodical Program «Pravozaschitnik».
Keywords: информационные технологии; техника; обучение; рукопашный; бой; курсанты; informative; technologies; technique; teaching; hand-to-hand; fight; students